The Fear: A Study of Consternation in Bradbury's “The Night” (1947) Through the Main Character - Asyida, Miqda Al Auza’i Ashfahany; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (LPPM Universitas Bina Sarana Informatika, 2025)
This study examines the fear in Ray Bradbury's The Night (1947) through the lens of the main character, Shorts. Using Fisher’s theory, this study focuses on how environmental factors and self-control regulate human emotion, especially fear. Thus, psychology in literature was applied to elaborate the fear in the short story. The study uses qualitative methods to investigate the narrative, revealing how external factors, such as the environment and the emotions of others, as well as internal factors, such as prior events and inner thoughts, influence Shorts' fear. The findings demonstrate how such elements influence human behavior, stressing the complex link between external situations and internal psychological states. Through Shorts's narrative, the study underscores the dynamic interaction between the external world and human emotion.